Walking in minimalist shoes is effective for strengthening foot muscles - Ridge, S. T.; Olsen, M. T.; Bruening, D. A.; Jurgensmeier, K.; Griffin, D.; Davis, I. S.; Johnson, A. W. (Medicine & Science in Sports & Exercise, 2019)
Introduction: Weakness of foot muscles may contribute to a variety of loading-related injuries. Supportive footwear may contribute to intrinsic foot muscle weakness by reducing the muscles` role in locomotion (e.g., absorbing forces and controlling motion). Increased stimulus to the foot muscles can be provided through a variety of mechanisms, including minimalist footwear and directed exercise.